2022
DOI: 10.1039/d1tc05488k
|View full text |Cite
|
Sign up to set email alerts
|

A luminescent 2,1,3-benzoxadiazole-decorated zirconium-organic framework as an exceptionally sensitive turn-on sensor for ammonia and aliphatic amines in water

Abstract: A new dicarboxylate ligand - 4,7-di(p-carboxyphenyl)-2,1,3-benzoxadiazole was synthesised and used for the preparation of 2,1,3-benzoxadiazole-decorated zirconim(IV)-based metal-organic framework UiO-68(bod). Single-crystal X-ray diffraction analysis revelead it to belong to UiO-68 family...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Due to the great emission behaviour and excellent chemical stability of nanosized HIAM-3007, especially under aqueous conditions, its potential application as a chemical sensor was explored. As reported, benzo[ c ][1,2,5]thiadiazole and its derivative-based LMOFs exhibited unprecedented sensitivity towards amine detection; 26,35–38 different kinds of amines (aliphatic amines: methanamine, ethylamine, propylamine, ethylenediamine, 1,4-diaminobutane, diethylamine, triethylamine and 1,4-diaminocyclohexane; aromatic amines: aniline, p -aminophenol, o -phenylenediamine, m -phenylenediamine and p -phenylenediamine) were thus chosen to test the response of nanosized HIAM-3007.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Due to the great emission behaviour and excellent chemical stability of nanosized HIAM-3007, especially under aqueous conditions, its potential application as a chemical sensor was explored. As reported, benzo[ c ][1,2,5]thiadiazole and its derivative-based LMOFs exhibited unprecedented sensitivity towards amine detection; 26,35–38 different kinds of amines (aliphatic amines: methanamine, ethylamine, propylamine, ethylenediamine, 1,4-diaminobutane, diethylamine, triethylamine and 1,4-diaminocyclohexane; aromatic amines: aniline, p -aminophenol, o -phenylenediamine, m -phenylenediamine and p -phenylenediamine) were thus chosen to test the response of nanosized HIAM-3007.…”
mentioning
confidence: 86%
“…4a, varying degrees of emission enhancements were obtained for different kinds of aliphatic amines at a concentration of 300 μM, which is consistent with reported works which showed that turn-on detection of aliphatic amines can be obtained using benzo[c][1,2,5]thiadiazole and its derivative-based LMOFs. 26,[35][36][37] These results can be ascribed to the strong interaction between aliphatic amines and naphtho[2,3-c][1,2,5]selenadiazole, which will restrict the motion of naphtho[2,3-c][1,2,5]selenadiazole, leading to reduced nonradiative recombination and enhanced emission. 26 The highest emission enhancement, 1.6 times compared with the blank sample, was recorded for diethylamine at a concentration of 300 μM, indicating that the sensitivity of HIAM-3007 for aliphatic amine detection is very low compared with the reported works.…”
mentioning
confidence: 99%
“…To test the real-life sensing applicability of Ni-btc NS, we performed an experiment with a model of contaminated wastewater. 15…”
Section: On-site Detectionmentioning
confidence: 99%
“…For any sensor to be viable for real-time application, along with rapid and high sensitivity, hydrolytic and thermal stability are crucial parameters. [15][16][17][18][19][20][21][22] Metal-organic frameworks (MOFs) have emerged as the most suitable choice for such sensing applications. 23 Metal-organic frameworks (MOFs) are porous inorganic and organic hybrid solids.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting 2,1,3-benzoxadiazole decorated electron-deficient Zr( iv )-based LMOF 7 for ‘turn-on’ fluorescence sensing of NH 3 was recently reported by the Potapov group. 50 LMOF 7 was prepared by heating a mixture of a dicarboxylate ligand, 4,7-di( p -carboxyphenyl)-2,1,3-benzoxadiazole ( L 7 ), and zirconium tetrachloride in DMF (Fig. 4(A)).…”
Section: Metal–organic Framework (Mof)-based Fluorescence Chemosensorsmentioning
confidence: 99%